A poly(3,4-ethylenedioxythiophene):poly(styrene sulfonic acid)/titanium oxide nanocomposite film synthesized by sol–gel assisted electropolymerization for electrochromic application - Lu, Jinlin (2016)
In this article, we report the facile synthesis of poly(3,4-ethylenedioxythiophene):poly(styrene sulfonic acid)/titanium dioxide (PEDOT:PSS/TiO2) nanocomposite film by sol–gel assisted electropolymerization. The structure, morphology and composition of the films were investigated by different techniques, such as Fourier transform infrared spectroscopy, X-ray diffraction, transmission electron microscopy, atomic force microscope and X-ray photoelectron spectroscopy. The PEDOT:PSS/TiO2 nanocomposite film was applied for electrochromic application. The results indicate that the PEDOT:PSS/TiO2 nanocomposite film exhibits a higher optical contrast and a much better stability as compared to PEDOT:PSS film. The significant performance enhancement can be attributed to the nanoscale particle size and uniform size distribution of PEDOT:PSS/TiO2 and the synergistic effect between the inorganic nano-TiO2 and organic PEDOT:PSS material.